Religiosity of Suburban People Community: A Case Study on Social Reality of Bonokeling Teaching in Indonesia - Yuspi, Lendra; Sholahuddin, Agus; Prianto, Budhy (Technium Social Sciences Journal, 2022)
This study aims to define and analyze the religiosity of the Bonokeling community and its religious background. This study is a qualitative study. The target of this study are disciples of the Bonokeling teaching in the area of Pekuncen Village in the Banyumas Regency. Sources are chosen by applying a snowball sampling technique. Data collection is completed by conducting interviews, observations and documentation. Our data is analysed using interactive methods of data collection, such as data condensation, data presentation, and conclusion. Bonokeling teaching was originally taught by a public figure known as Kyai Bonokeling. Although Bonokeling principles are based on the religion of Islam, it only practices 3 Pillars of Islam, which are creed (confession of faith), fasting and zakat. Disciples of Bonokeling teaching get to know the principles of Bonokeling through their parents, some of whom are direct descendants and some are loyal disciples of Kyai Bonokeling. In experiencing or behaving religiously, the majority of Bonokeling disciples practice the ritual obediently and solemnly although they do not fully understand the significance of the instruments used and the prayers they chant during the rituals. Disciples of Bonokeling teaching do not just recite and say amen to prayers. As time progressed, disciples of Bonokeling left their denomination and started to worship in accordance with Islamic sharia. These changes happen as education advances, but also due to socio-cultural exposures once they leave their hometown to study or work outside the region. The existence of the Bonokeling denomination is slowly vanishing and only its cultural activities are left for people to practice. Meanwhile, the loyal disciples who have been practicing for a long time (until the existing generations succeed them) live in remote areas.